Acts of Conspicuous Compassion : Performance Culture and American Charity Practices - Moeschen, Sheila C. (Book collections on Project MUSE., 2013)
Charity has been a pervasive and influential concept in American culture, and has also served an important ideological purpose, helping people articulate their sense of individual and national identity. But what, exactly, compels our benevolence? In a social moment when countless worthy causes and deserving groups clamor for attention, it is worth examining how our culture generates the exchange of sympathy commonly experienced as "charity." This book investigates the historical and continuing relationship between performance culture and the cultivation of charitable sentiment, exploring the distinctive practices that have evolved to make the plea for charity legible and compelling. From the work of 19th-century melodramas to the televised drama of transformation and redemption in reality TV's Extreme Makeover: Home Edition, this book charts the sophisticated strategies that various charity movements have employed to make organized benevolence seem attractive, exciting, and seemingly uncomplicated. The author sheds light on the legacy and involvement of disabled people within charity - specifically, the articulation of performance culture as a vital theoretical framework for discussing issues of embodiment and identity, a framework that dislodges previously held notions of the disabled existing as passive "objects" of pity. This work gives rise to a more complicated and nuanced discussion of the participation of the disabled community in the charity industry, of the opportunities afforded by performance culture for disabled people to act as critical agents of charity, and of the ethical and political issues that arise from employing performance methodology in a culture with increased appetites for voyeurism, display, and complex spectacle.